Measuring Envy Level among Students of Faculty of Medicine - Eka Nurhayati; Susan Fitriyana; Eva Rianti Indrasari (Global Medical & Health Communication (GMHC), 2020)
Envy is a negative emotion that painful and unpleasant, caused by feelings of inferiority when someone compared themselves to others. Envy is divided into benign and malicious envy. Benign envy could be leverage to motivate someone to improve themselves until they reach or even exceed the envied person’s level. In contrast, malicious is destructive that someone could do anything to pull the envied person down to the same level as themselves or even lower. This study aimed to measure benign and malicious envy among the students of the Faculty of Medicine Universitas Islam Bandung. It was a descriptive study involving 152 students. Measurement made using the Benign and Malicious Envy Scale (BeMaS), which uses 6 points Likert scale during November 2019. Data analysis using Microsoft Excel. The study results showed envy among the students dominated by positive or productive envy, the mean value for benign envy (4.57), and malicious envy (1.92). It showed that benign envy push students to be more competitive rather than destructive envy. The conclusion of this study that the level of envy students of the Faculty of Medicine Universitas Islam Bandung dominated by benign envy. The faculty is responsible for developing strategies to increase the benign envy level and control the malicious envy level. PENGUKURAN TINGKAT IRI PADA MAHASISWA SEBUAH FAKULTAS KEDOKTERANIri adalah emosi negatif menyakitkan dan tidak menyenangkan yang diakibatkan oleh perasaan inferior ketika membandingkan diri dengan orang lain. Iri terbagi atas benign envy dan malicious envy. Benign envy bersifat memotivasi seseorang untuk terus memperbaiki diri sampai mencapai bahkan melebihi apa yang dimiliki kompetitornya. Sebaliknya, malicious envy bersifat destruktif ketika seseorang berupaya untuk menarik kompetitornya ke level yang sama dengan dirinya atau bahkan lebih rendah. Penelitian ini bertujuan mengukur tingkat benign dan malicious envy pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung. Penelitian ini merupakan penelitian deskriptif dengan melibatkan 152 mahasiswa sebagai subjek penelitian. Pengukuran dilakukan menggunakan Benign and Malicious Envy Scale (BeMaS) selama November 2019  menggunakan 6 poin Skala Likert dan analisis data menggunakan Microsoft Excel. Hasil penelitian menunjukkan bahwa rerata benign envy (4,57) lebih tinggi dibanding dengan malicious envy (1,92). Hal ini menunjukkan bahwa iri yang bersifat positif atau produktif jauh lebih tinggi dibanding dengan nilai iri yang bersifat destruktif. Simpulan penelitian ini adalah bahwa tingkat iri pada mahasiswa Fakultas Kedokteran Universitas Islam Bandung lebih dominan pada benign envy dibanding dengan malicious envy. Tugas fakultas adalah mengembangkan strategi agar dapat meningkatkan nilai benign envy serta berupaya mengendalikan tingkat malicious envy.